Analysis of Rainwater Harvesting Methods for Optimizing Small Island Areas: A Case Study in Selaru Island, Indonesia - Rumihin, Ony Frengky; Makarim, Chaidir Anwar; Pranoto, Wati Asrinigsih (Westscience Press, 2024)
Water management on islands has an important role because of their limited features. Although each island has different features (size, isolation, geology and topography, climate and hydrology, economic development, etc.) – all affecting water resources and management, all islands face many of the same water-related issues and challenges. This condition is influenced by population growth triggered by the development of natural resources. This research aims to ensure that the rainwater harvesting method as an alternative water source can fulfill distribution deficiencies while maintaining the ecological conditions of small island areas. Water availability is analyzed using the F.J. Mock method, and the existing sources are analyzed using the RWH method. Based on guidelines, the analysis of domestic water needs is 65 L/person/day. The analysis continues with the existing distribution scenario. The results show that the Adaut sub-watershed and the Namtabung sub-watershed are predicted to experience water shortages, and the combined distribution scenario of existing sources and the RWH method can be a solution to overcome water shortages. The RWH method can achieve optimal water distribution in Selaru Island until 2040.